2021
DOI: 10.3390/su13189996
|View full text |Cite
|
Sign up to set email alerts
|

Employee Satisfaction, Corporate Social Responsibility and Financial Performance

Abstract: This study explores the extent to which employee turnover, a proxy variable to employee loyalty, helps mediate the relationship between Taiwanese firms’ corporate social responsibility (CSR) performance and financial outcome. The results show that a firm’s CSR performance is negatively correlated with employee turnover and turnover variability, and moreover, employee turnover is negatively correlated with a firm’s financial performance. The result is especially noteworthy for studies regarding Taiwanese compan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…They found a general positive relationship between employer branding and job satisfaction, organizational commitment and psychological contract. And most recently, Chang et al (2021), in a study of Taiwanese firms, found that a firm's CSR performance was negatively associated with employee turnover, which, in turn, was negatively associated with the firm's financial performance.…”
Section: Exploratory Factors Related To Best Companies To Work Formentioning
confidence: 99%
“…They found a general positive relationship between employer branding and job satisfaction, organizational commitment and psychological contract. And most recently, Chang et al (2021), in a study of Taiwanese firms, found that a firm's CSR performance was negatively associated with employee turnover, which, in turn, was negatively associated with the firm's financial performance.…”
Section: Exploratory Factors Related To Best Companies To Work Formentioning
confidence: 99%
“…Small and medium enterprises (SMEs) performance issues have drawn the interest of scholars from various disciplines and perspectives (Joensuu-Salo et al, 2018;Maes et al, 2005;Sadiq et al, 2020). Two performance measures are notable in the literature: financial measures, such as profit, turnover, return on investment, productivity (Saad and Patel, 2006;Maes et al, 2005;Shamsuddin et al, 2018) and non-financial measures, including the number of employees, communication, learning, trust, stakeholder satisfaction, and competitive position (Chang et al, 2021;Garrigos-Simon et al, 2005). However, Murphy et al (1996) discover that the most frequently used measures are predominantly economic.…”
Section: Smes Performancementioning
confidence: 99%
“…In addition to these indicators, they also include measures of customer satisfaction and ES. Some scholars have also pointed out that in the field of CSR, the financial performance of enterprises is often confused with corporate performance, but strictly speaking, the scope of corporate performance is larger than that of financial performance, which refers specifically to the achievement of economic goals [13].…”
Section: Literature Reviewmentioning
confidence: 99%